Challenges and successes in the sustainment of Dutch community-level smoking cessation interventions for residents with a low socioeconomic position - Nikita L. Poole; Floor A. van den Brand; Marc C. Willemsen; Gera E. Nagelhout (BMC, 2023)
Abstract Background When health promotion interventions are implemented, the gains are often short-lived, as interventions are seldom successfully sustained. The current study explores how and under what conditions community-level smoking cessation interventions for people with a lower socioeconomic position can be sustained, drawing upon interventions delivered in Dutch neighbourhoods with a predominantly low socioeconomic position. Methods We conducted 15 semi-structured interviews with key stakeholders from three Dutch community-level smoking cessation interventions implemented at least three years prior. The topic guide was developed based on the Determinants of Innovation framework and transcripts were analysed thematically. Results We identified several factors that promote the sustainment of smoking cessation community-level interventions: 1) structural, long-term funding through the commitment of health insurers and policy makers; 2) continued stakeholder enthusiasm and involvement; 3) training and time for professionals to discuss smoking cessation, thereby also increasing the visibility of the intervention for professionals and residents; 4) integrating the intervention with existing initiatives and adapting it to be compatible with current working practices of executive staff; and 5) planning for sustainment as a team from the outset. Conclusions The current study highlights challenges and successes in intervention sustainment for people with a lower socioeconomic position. Lack of structural funding was one of the most challenging aspects for intervention sustainment in which health insurers and policy makers can play an important role. Planning for sustainment from the outset would enable intervention coordinators to consider the abovementioned factors early on. This need not be done alone but can best be discussed within a team of stakeholders.